HUBUNGAN KAUSALITAS PARIWISATA DAN PERTUMBUHAN EKONOMI DI INDONESIA: ANALISIS PANEL VAR - Maulana, Rienalvyn Andri; Prasetyia, Ferry (Journal of Development Economic and Social Studies, 2023)
Tourism continues to experience growth and diversification to become one of the largest and fastest growing economic sectors in the world. The tourism industry is also increasingly playing an important role in the economy in many countries, including Indonesia. Therefore, this research aims to determine the causality relationship between tourism and economic growth in Indonesia using VAR Panel Analysis. By using panel data from 10 provinces in Indonesia in the period of 2009-2018, the VAR Panel analysis found that tourism and economic growth in Indonesia have a two-way causal relationship. Nevertheless, causality relationships are formed with different directions of influence and timeframes.